Short-term outcomes analysis of modified Karlsson procedure in chronic lateral ankle joint instability cases with generalized joint laxity - Zhen Shen; Guangbin Duan; Yongyong Dong; Yadi Liu; Chencheng Zhao; Jinjun Zhong; Huihui Wang; Yang Li; Haoran Shi; Leibo Yang (BMC Musculoskeletal Disorders)
Abstract Background Generalized joint laxity (GJL) may affect chronic lateral ankle instability (CLAI) treatment. Short-term results of the arthroscopic-assisted modified Karlsson technique in CLAI were compared for GJL and non-GJL cases. Methods This retrospective analysis included 75 CLAI patients admitted to Jincheng People’s Hospital from August 2019 to August 2023. Patients were diagnosed with CLAI based on clinical history, physical examination, and imaging findings. Twenty-five patients had concomitant GJL (hypermobile group), while fifty did not (non-hypermobile group). Both groups underwent arthroscopic-assisted modified Karlsson surgery. General characteristics and joint function were compared 6 months postoperatively. Ankle function was assessed using the anterior drawer test (ADT), AOFAS ankle score, and Karlsson score before and after surgery. Results Preoperative ADT displacement was similar between groups (9.8 ± 1.9 vs. 9.5 ± 1.7 mm, P = 0.51), but at 6 months postoperatively, the hypermobile group exhibited greater residual laxity (4.2 ± 1.3 vs. 2.8 ± 0.9 mm, P = 0.001). Functional scores improved significantly in both groups (P < 0.05), though the hypermobile group had lower final AOFAS (82.4 ± 6.3 vs. 88.1 ± 5.7, P = 0.003) and Karlsson scores (80.5 ± 7.2 vs. 86.3 ± 6.8, P = 0.004) compared to controls.hypermobile group. Conclusion All patients had increased ankle function and clinical efficacy after the arthroscopy-assisted modified Karlsson treatment. Concomitant GJL patients had worse short-term results than those without GJL.